Pengaruh Stakeholder terhadap Corporate Social Responsibility Disclosure atas Sektor Perusahaan Index LQ45 & ESG Leader - Novianti, Ria; Meiden, Carmel (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study is an empirical study to examine the influence of female board of commissioners, foreign institutions, media, employees, and managerial ownership on Corporate Social Responsibility (CSR) disclosure. The object of the study is manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sample of companies is 22 companies per year. With a total sample of 88 companies per 4 years of observation. The research analysis method used is descriptive statistical analysis test, classical assumption test which includes: normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, as well as hypothesis test which includes: multiple determination coefficient test (R2), F statistical test, and statistical test (t). The regression analysis used in this study is multiple linear regression analysis. The results of this study indicate that female board of commissioners, employees and managerial ownership do not affect Corporate Social Responsibility (CSR) disclosure. While foreign institutions and media have a positive effect on Corporate Social Responsibility (CSR) disclosure.